2018
DOI: 10.3389/fpsyg.2018.00301
|View full text |Cite
|
Sign up to set email alerts
|

Gender Gaps in Letter-Sound Knowledge Persist Across the First School Year

Abstract: Literacy is the cornerstone of a primary school education and enables the intellectual and social development of young children. Letter-sound knowledge has been identified as critical for developing proficiency in reading. This study explored the development of letter-sound knowledge in relation to gender during the first year of primary school. 485 Norwegian children aged 5–6 years completed assessment of letter-sound knowledge, i.e., uppercase letters- name; uppercase letter -sound; lowercase letters- name; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…Transitioning to the present day, we now look beyond national and international reports and consider relevant, individual studies focusing specifically on early literacy and gender. Concurrent with large scale reports, the majority of individual studies have indicated evidence of girls' higher performance in early literacy (e.g., Clark & Kragler, 2005;Chipere, 2014;Lummis & Stevenson, 1990;Phillips, Norris, Osmond, & Maynard, 2002;Ready, LoGerfo, Burkam, & Lee, 2005;Sigmundsson, Dybfest Eriksen, Ofteland, & Haga, 2018). It is also essential to observe that such findings are not idiosyncratic but represent trends that have occurred over decades, across nations and languages.…”
Section: A Closer Examination Of Gender and Early Literacy Skillsmentioning
confidence: 94%
See 2 more Smart Citations
“…Transitioning to the present day, we now look beyond national and international reports and consider relevant, individual studies focusing specifically on early literacy and gender. Concurrent with large scale reports, the majority of individual studies have indicated evidence of girls' higher performance in early literacy (e.g., Clark & Kragler, 2005;Chipere, 2014;Lummis & Stevenson, 1990;Phillips, Norris, Osmond, & Maynard, 2002;Ready, LoGerfo, Burkam, & Lee, 2005;Sigmundsson, Dybfest Eriksen, Ofteland, & Haga, 2018). It is also essential to observe that such findings are not idiosyncratic but represent trends that have occurred over decades, across nations and languages.…”
Section: A Closer Examination Of Gender and Early Literacy Skillsmentioning
confidence: 94%
“…When considering findings from only the first year of school, initial gender differences favoring girls appear meaningful and stable. For example, Sigmundsson et al (2018) and Clark and Kragler (2005) document that girls' literacy advantages stay consistent from the beginning to the end of the first year. Furthermore, Ready et al (2005) andMcCoach, O'Connell, Reis, andLevitt (2006) documented that girls enter with an advantage and then subsequently learn more than their male peers in the first year (i.e.…”
Section: Persistence Of Early Gender Differences In Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of a faster pace of letter instruction 6 When children first start school, their letter knowledge varies greatly, both in terms of which letters they know and how many (Justice et al, 2006;Piasta, 2014;Sigmundsson, Eriksen, Ofteland, & Haga, 2017). There is also a gender difference in letter knowledge favouring girls, both at school entry and at the end of the first year (Sigmundsson, Dybfest Eriksen, Ofteland, & Haga, 2018). The heterogeneity of classes represents a challenge to teachers when it comes to meeting the children's individual needs (Justice et al, 2006;Piasta, 2014).…”
Section: Letter Instructionmentioning
confidence: 99%
“…Girls have been shown to outperform and gain literacy skills at a faster rate than boys in the early school years (Below et al, 2010;Clark & Kragler, 2005;Deasley et al, 2018;Harper & Pelletier, 2008;Lee & Al Otaiba, 2015). More precisely, gender differences in vocabulary growth (Huttenlocher et al, 1991), phonological awareness (Lundberg et al, 2012), letter-sound knowledge (Sigmundsson et al, 2017(Sigmundsson et al, , 2018, and letter-writing scores (Puranik et al, 2013) have been found among children in preschool and first grade. These gender differences occur very early.…”
Section: The Effects Of Individual and Sociodemographic Variables On mentioning
confidence: 99%